Epidemiology of injuries in judo: a cross-sectional survey of severe injuries based on time loss and reduction in sporting level. Issue 17 (26th April 2017) - Akoto, Ralph; Lambert, Christophe; Balke, Maurice; Bouillon, Bertil; Frosch, Karl-Heinz; Höher, Jürgen
Abstract : Background: Sport injury severity can be detected by duration of time loss and reduction of sporting performance. Aim: To detect injury type-specific time loss duration and sporting performance reduction in judo. Methods: An online survey of active and former judo athletes was conducted (exclusion criterion: incomplete questionnaire). Only injuries causing more than 3 weeks' time loss were recorded. Athletes classified themselves into performance classes. Injury type-specific frequencies were recorded according to gender, age and performance level. Injury severity was assessed by time loss duration and performance reduction. Results: The study included 4659 athletes (65% male, 38% competitive sports). The most commonly injured body regions were the upper extremity (41%) and the lower extremity (39%). Anterior cruciate ligament (ACL) ruptures were the most severe injury type (time loss: 4% of cases 3–6 weeks, 6% 6–12 weeks, 26% 3–6 months, 32% 6–9 months, 18% 9–12 months, 14%>12 months; performance reduction: 32% same level, 39% slightly reduced, 24% strongly reduced, 5% stopped judo). The second most severe type of injury was a vertebral disc prolapse (time loss: 26% 3–6 weeks, 31% 6–12 weeks, 20% 3–6 months, 7% 6–9 months, 3% 9–12 months 13%>12 months; reduction of sporting performance: 39% same level, 34% slightly reduced, 20% strongly reduced, 8% stopped judo). Conclusion: Across genders and performance levels, ACL ruptures and vertebral disc prolapses were the most severe injuries with respect to time loss and sporting performance reduction.